Investigating Black Soldier Fly Larval (Hermetia illucens) Frass Applications as a Partial Peat Replacement and Liquid Fertilizer in Brassicaceae Crop Production - Maria Y. Chavez; Armando Villa Ignacio; Joshua K. Craver; Jennifer Bousselot (Agrochemicals)
Insect frass is the left-over side stream from mass rearing insects as food and feed. Research indicates that black soldier fly, Hermetia illucens, larvae (BSFL) frass can improve the yield of leafy greens while also increasing nutrient uptake. Two studies evaluated the impact of BSFL frass on two Brassicaceae crops: kale (Brassica oleracea) and mustard (Sinapis alba). In Study 1, greenhouse potting mixes comprised of 10% BSFL frass produced kale and mustard fresh and dry weights, relative chlorophyll concentrations, and nitrogen concentration in plant tissues that were comparable to a 100% peat mix control. In mustard tissue, phosphorus and potassium concentrations were higher in the BSFL 10% treatment compared to the control. This provides further motive for incorporating frass into peat-based substrates to reduce peat consumption and extraction. In Study 2, Liquid BSFL frass tea was applied to kale in an outdoor container study. The frass tea only treatment produced the worst outcomes for yield. However, a mixture of frass tea and traditional fertilizer resulted in comparable yield to a control provided the same volume in solely fertilizer. With further research, frass tea could be supplemented to reduce conventional fertilizers.